Effect of fatigue on the coordination variability in rowers - Talty, P.; Anderson, R. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
According to the Dynamical Systems Theory (DST), movement variability is an essential feature of human motor behaviour. This theory of motor control has led to a paradigm shift in sport biomechanics research. Whereas previously, variability in sports biomechanics data was viewed as erroneous and in need of elimination, more recently the existence, amount and effect of variability on different aspects of sports biomechanics has been considered (Hamill et al., 1999). Numerous studies have also considered the effect of fatigue on coordination. Aune et al. (2008) found that fatigue induced a reduction in variability in segment positioning for highly skilled table-tennis players. Also a high level of performance was maintained by reducing racket velocity and thus altering the racket position at the point of racket-ball contact. In rowing, the athlete is seated throughout the event the back is continuously in a flexed position, this leads to high levels of lower back pain (LBP) among rowers (Perich et al., 2006). The current study will investigate coordination variability using an ergometer based rowing protocol designed to induce fatigue. The current research question is how does coordination variability react to fatigue and how does this relate to LBP.